The cholesterol metabolite 27 hydroxycholesterol facilitates breast cancer metastasis through its actions on immune cells - Amy E. Baek (Nature Portfolio, 2017)
High cholesterol is a risk factor for breast cancer recurrence. Here the authors show that cholesterol promotes breast cancer metastasis via its metabolite 27-hydroxycholesterol (27HC) that acts on immune myeloid cells residing at the distal metastatic sites, thus promoting an immune suppressive environment.